the explanation of opposition of Thought and act in Farabie's and Avecina's view - fattaneh tavanapanah; nadia maftooni (اخلاق وحیانی)
The soul’s tendency as the origin of intentional act is considered by Farabi and Avesina. the votes effects of capricious wind and the acts consequences of tendencies causes the importance of discussion about the emotional acts origin. Both Farabis and Avesina considers the apprehensions of emotions and tendencies and acts consequences in common people as basis for societies need to the rhetoric in behaviors dimension. The individuals encouragement to the intentional act according to the take part peace of heart and impulsion, tendency desire and etc. in creating act causes the appearance of the role of persuasion and affections of it in his dimension and the attract tendencies. The persuasions position in this dimension could consider in the basis such as persuasion as the foundation of the intentional acts, the effects tendencies of persuasion and persuasive affairs and the consideration impulsions dimension and emotional persuasion and rhetoric such affections create a type of aspiration and the precedence the type of act. That it don’t perform in the absence of such affairs. Persuasion could be very important in alteration, conciliation and in order to direction of the acts in emotional dimension.